Barriers to Institutional Childbirth in Rumbek North County, South Sudan: A Qualitative Study. - Calistus Wilunda; Chiara Scanagatta; Giovanni Putoto; Risa Takahashi; Francesca Montalbetti; Giulia Segafredo; Ana Pilar Betrán (PLoS ONE)
Background South Sudan has one of the world's poorest health indicators due to a fragile health system and a combination of socio-cultural, economic and political factors. This study was conducted to identify barriers to utilisation of institutional childbirth services in Rumbek North County. Methods Data were collected through 14 focus group discussions with 169 women and 45 men, and 18 key informant interviews with community leaders, staff working in health facilities, traditional birth attendants, and the staff of the County Health Department. Data were analysed using inductive content analysis. Results The barriers to institutional childbirth were categorised under four main themes: 1) Issues related to access and lack of resources: long distance to health facilities, lack of transportation means, referral problems, flooding and poor roads, and payments in health facilities; 2) Issues related to the socio-cultural context and conflict: insecurity, influence of the husband, lack of birth preparedness, domestic chores of women, influence of culture; 3) Perceptions about pregnancy and childbirth: perceived benefit of institutional childbirth, low childbirth risk perception, and medicalisation of childbirth including birth being perceived to be natural, undesirable birth practices, privacy concerns, and fear of caesarean section; and 4) Perceptions about the quality of care: inadequate health facility infrastructure and perceived neglect during admission. Conclusions Multiple factors hinder institutional childbirth in Rumbek North. Some of the factors such as insecurity and poor roads are outside the scope of the health sector and will require a multi-sectoral approach if childbirth services are to be made accessible to women. Detailed recommendations to increase utilisation of childbirth services in the county have been suggested.